The impact of persistent COVID-19-related chemosensory dysfunction on quality of life, appetite and hunger: The COVORTS study - Birgit van Dijk; Elbrich M. Postma; Wilbert M. Boek; Digna M.A. Kamalski; Sanne Boesveldt (Appetite, 2026)

Integration of six field studies to assess soil suppressiveness against Globisporangium ultimum under different management practices - Viola Kurm; Mirjam T. Schilder; Johnny H. M. Visser; Joeke Postma (Biology and Fertility of Soils, 2026)

FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

Agricultural Supervisors’ Perspectives on Occupational Wildfire Smoke Rules - Julie Postma; Molly Parker; Sheila Hurst; Juliana Romo; Janessa M. Graves (Journal of Agromedicine, 2025)

P28-12 Stronger together: achieving scalability for a novel in vitro human male reproductive toxicity assay by deep learning image analysis pipelines - R.J. Postma; M. Trimp; S.M. Chuva de Sousa Lopes (Toxicology Letters, 2025)

Agricultural Employer Perspectives on Occupational Wildfire Smoke Rules - Molly Parker; Janessa M. Graves; Lois James; Julie Postma (Journal of Agromedicine, 2025)

Back to the roots: standardizing root length density terminology - Tomke S. Wacker; Frederik van der Bom; Benjamin M. Delory; Doris Vetterlein; Johannes A. Postma; Kerstin A. Nagel; Andrea Schnepf; Dorte Bodin Dresbøll (Plant and Soil, 2025)
The number of studies investigating root length has increased, particularly in the context of root length measurements observed through windows such as minirhizotrons and rhizoboxes. However, there are currently two obstacles constraining their broader utility: (1) the absence of standardized terminology or units for root length data, and (2) the translation from two-dimensional (2D) to three-dimensional (3D) data. Here, we delineate the fundamental disparities between root length measurements obtained from observation windows and via volumetric soil sampling and propose the adoption of more precise terminology to distinguish 2D planar (pRLD) from 3D volumetric (vRLD) root length density measurements. This differentiation should be accompanied with the use of standardized units and should not endeavour to make blanket conversions between dimensions unless this is supported by specific calibration data.

Identifying priority heat-risk areas in Granada, Spain, using InVEST and landscape metrics - Carson Silveira; Nuria Pistón; Javier Martínez-López; Domingo Alcaraz-Segura; Thedmer Postma; Juan M. López-Torralbo; Regino Zamora (Urban Forestry & Urban Greening, 2025)

Predicting Cognitive Functioning for Patients with a High-Grade Glioma: Evaluating Different Representations of Tumor Location in a Common Space - S. M. Boelders; W. De Baene; E. Postma; K. Gehring; L. L. Ong (Neuroinformatics, 2024)
Cognitive functioning is increasingly considered when making treatment decisions for patients with a brain tumor in view of a personalized onco-functional balance. Ideally, one can predict cognitive functioning of individual patients to make treatment decisions considering this balance. To make accurate predictions, an informative representation of tumor location is pivotal, yet comparisons of representations are lacking. Therefore, this study compares brain atlases and principal component analysis (PCA) to represent voxel-wise tumor location. Pre-operative cognitive functioning was predicted for 246 patients with a high-grade glioma across eight cognitive tests while using different representations of voxel-wise tumor location as predictors. Voxel-wise tumor location was represented using 13 different frequently-used population average atlases, 13 randomly generated atlases, and 13 representations based on PCA. ElasticNet predictions were compared between representations and against a model solely using tumor volume. Preoperative cognitive functioning could only partly be predicted from tumor location. Performances of different representations were largely similar. Population average atlases did not result in better predictions compared to random atlases. PCA-based representation did not clearly outperform other representations, although summary metrics indicated that PCA-based representations performed somewhat better in our sample. Representations with more regions or components resulted in less accurate predictions. Population average atlases possibly cannot distinguish between functionally distinct areas when applied to patients with a glioma. This stresses the need to develop and validate methods for individual parcellations in the presence of lesions. Future studies may test if the observed small advantage of PCA-based representations generalizes to other data.

Innovating transcriptomics for practitioners in freshwater fish management and conservation: best practices across diverse resource-sector users - C. A. D. Semeniuk; K. M. Jeffries; T. Li; C. M. Bettles; S. J. Cooke; B. A. Dufour; E. A. Halfyard; J. W. Heath; K. Keeshig; N. E. Mandrak; A. J. Muir; L. Postma; et al. (Reviews in Fish Biology and Fisheries, 2022)

Circumpolar phylogeography and demographic history of beluga whales reflect past climatic fluctuations - Mikkel Skovrind; Marie Louis; Michael V. Westbury; Cristina Garilao; Kristin Kaschner; José Alfredo Samaniego Castruita; Shyam Gopalakrishnan; Steen Wilhelm Knudsen; James S. Haile; Love Dalén; Ilya G. Meshchersky; Olga V. Shpak; et al. (Molecular Ecology, 2021)
Several Arctic marine mammal species are predicted to be negatively impacted by rapid sea ice loss associated with ongoing ocean warming. However, consequences for Arctic whales remain uncertain. To investigate how Arctic whales responded to past climatic fluctuations, we analysed 206 mitochondrial genomes from beluga whales ( Delphinapterus leucas ) sampled across their circumpolar range, and four nuclear genomes, covering both the Atlantic and the Pacific Arctic region. We found four well‐differentiated mitochondrial lineages, which were established before the onset of the last glacial expansion ~110 thousand years ago. Our findings suggested these lineages diverged in allopatry, reflecting isolation of populations during glacial periods when the Arctic sea‐shelf was covered by multiyear sea ice. Subsequent population expansion and secondary contact between the Atlantic and Pacific Oceans shaped the current geographic distribution of lineages, and may have facilitated mitochondrial introgression. Our demographic reconstructions based on both mitochondrial and nuclear genomes showed markedly lower population sizes during the Last Glacial Maximum (LGM) compared to the preceding Eemian and current Holocene interglacial periods. Habitat modelling similarly revealed less suitable habitat during the LGM (glacial) than at present (interglacial). Together, our findings suggested the association between climate, population size, and available habitat in belugas. Forecasts for year 2100 showed that beluga habitat will decrease and shift northwards as oceans continue to warm, putatively leading to population declines in some beluga populations. Finally, we identified vulnerable populations which, if extirpated as a consequence of ocean warming, will lead to a substantial decline of species‐wide haplotype diversity.

Life‐history trade‐offs and the genetic basis of fitness in Arabidopsis thaliana - Thomas James Ellis; Froukje M. Postma; Christopher G. Oakley; Jon Ågren (Molecular Ecology, 2021)
Resources allocated to survival cannot be used to increase fecundity, but the extent to which this trade‐off constrains adaptation depends on overall resource status. Adaptation to local environmental conditions may therefore entail the evolution of traits that increase the amount of resources available to individuals (their resource status or ‘condition’). We examined the relative contribution of trade‐offs and increased condition to adaptive evolution in a recombinant inbred line population of Arabidopsis thaliana planted at the native sites of the parental ecotypes in Italy and Sweden in 2 years. We estimated genetic correlations among fitness components based on genotypic means and explored their causes with QTL mapping. The local ecotype produced more seeds per fruit than did the non‐local ecotype, reflected in stronger adaptive differentiation than was previously shown based on survival and fruit number only. Genetic correlations between survival and overall fecundity, and between number of fruits and number of seeds per fruit, were positive, and there was little evidence of a trade‐off between seed size and number. Quantitative trait loci for these traits tended to map to the same regions of the genome and showed positive pleiotropic effects. The results indicate that adaptive differentiation between the two focal populations largely reflects the evolution of increased ability to acquire resources in the local environment, rather than shifts in the relative allocation to different life‐history traits. Differentiation both in phenology and in tolerance to cold is likely to contribute to the advantage of the local genotype at the two sites.

Shrubs and Degraded Permafrost Pave the Way for Tree Establishment in Subarctic Peatlands - Juul Limpens; Thijs P. M. Fijen; Iris Keizer; Johan Meijer; Fanny Olsthoorn; Ana Pereira; Roel Postma; Mariette Suyker; Harri Vasander; Milena Holmgren (Ecosystems, 2021)
Arctic and subarctic ecosystems are changing rapidly in species composition and functioning as they warm twice as fast as the global average. It has been suggested that tree-less boreal landscapes may shift abruptly to tree-dominated states as climate warms. Yet, we insufficiently understand the conditions and mechanisms underlying tree establishment in the subarctic and arctic regions to anticipate how climate change may further affect ecosystem structure and functioning. We conducted a field experiment to assess the role of permafrost presence, micro-topography and shrub canopy on tree establishment in almost tree-less subarctic peatlands of northern Finland. We introduced seeds and seedlings of four tree-line species and monitored seedling survival and environmental conditions for six growing seasons. Our results show that once seedlings have emerged, the absence of permafrost can enhance early tree seedling survival, but shrub cover is the most important driver of subsequent tree seedling survival in subarctic peatlands. Tree seedling survival was twice as high under an intact shrub canopy than in open conditions after shrub canopy removal. Under unclipped control conditions, seedling survival was positively associated with dense shrub canopies for half of the tree species studied. These strong positive interactions between shrubs and trees may facilitate the transition from today’s treeless subarctic landscapes towards tree-dominated states. Our results suggest that climate warming may accelerate this vegetation shift as permafrost is lost, and shrubs further expand across the subarctic.

Imaging the role of blood–brain barrier disruption in normal cognitive ageing - Inge C. M. Verheggen; Joost J. A. de Jong; Martin P. J. van Boxtel; Alida A. Postma; Jacobus F. A. Jansen; Frans R. J. Verhey; Walter H. Backes (GeroScience, 2020)
To investigate whether blood–brain barrier (BBB) disruption is a potential mechanism of usual age-related cognitive decline, we conducted dynamic contrast–enhanced (DCE) MRI to measure BBB leakage in a healthy sample, and investigated the association with longitudinal cognitive decline. In a sample of neurologically and cognitively healthy, older individuals, BBB leakage rate in the white and grey matter and hippocampus was measured using DCE MRI with pharmacokinetic modelling. Regression analysis was performed to investigate whether the leakage rate was associated with decline in cognitive performance (memory encoding, memory retrieval, executive functioning and processing speed) over 12 years. White and grey matter BBB leakages were significantly associated with decline in memory retrieval. No significant relations were found between hippocampal BBB leakage and cognitive performance. BBB disruption already being associated with usual cognitive ageing, supports that this neurovascular alteration is a possible explanation for the cognitive decline inherent to the ageing process. More insight into BBB leakage during the normal ageing process could improve estimation and interpretation of leakage rate in pathological conditions. The current results might also stimulate the search for strategies to maintain BBB integrity and help increase the proportion people experiencing successful ageing. Netherlands Trial Register number: NL6358, date of registration: 2017-03-24.

Increase in blood–brain barrier leakage in healthy, older adults - Inge C. M. Verheggen; Joost J. A. de Jong; Martin P. J. van Boxtel; Ed H. B. M. Gronenschild; Walter M. Palm; Alida A. Postma; Jacobus F. A. Jansen; Frans R. J. Verhey; Walter H. Backes (GeroScience, 2020)
Blood–brain barrier (BBB) breakdown can disrupt nutrient supply and waste removal, which affects neuronal functioning. Currently, dynamic contrast-enhanced (DCE) MRI is the preferred in-vivo method to quantify BBB leakage. Dedicated DCE MRI studies in normal aging individuals are lacking, which could hamper value estimation and interpretation of leakage rate in pathological conditions. Therefore, we applied DCE MRI to investigate the association between BBB disruption and age in a healthy sample. Fifty-seven cognitively and neurologically healthy, middle-aged to older participants (mean age: 66 years, range: 47–91 years) underwent MRI, including DCE MRI with intravenous injection of a gadolinium-based contrast agent. Pharmacokinetic modeling was applied to contrast concentration time-curves to estimate BBB leakage rate in each voxel. Subsequently, leakage rate was calculated in the white and gray matter, and primary (basic sensory and motor functions), secondary (association areas), and tertiary (higher-order cognition) brain regions. A difference in vulnerability to deterioration was expected between these regions, with especially tertiary regions being affected by age. Higher BBB leakage rate was significantly associated with older age in the white and gray matter, and also in tertiary, but not in primary or secondary brain regions. Even in healthy individuals, BBB disruption was stronger in older persons, which suggests BBB disruption is a normal physiologically aging phenomenon. Age-related increase in BBB disruption occurred especially in brain regions most vulnerable to age-related deterioration, which may indicate that BBB disruption is an underlying mechanism of normal age-related decline. Netherlands Trial Register number: NL6358, date of registration: 2017-03-24.

Plant density modifies root system architecture in spring barley (Hordeum vulgare L.) through a change in nodal root number - V. L. Hecht; V. M. Temperton; K. A. Nagel; U. Rascher; R. Pude; Johannes A. Postma (Plant and Soil, 2019)

Solubility Constraints on Aquatic Ecotoxicity Testing of Anionic Surfactants - J. Hammer; A. M. Tukker; J. F. Postma; J. J. -H. Haftka; J. L. M. Hermens; P. de Voogt; M. H. S. Kraak (Bulletin of Environmental Contamination and Toxicology, 2018)

Among‐year variation in selection during early life stages and the genetic basis of fitness in Arabidopsis thaliana - Froukje M. Postma; Jon Ågren (Molecular Ecology, 2018)
Incomplete information regarding both selection regimes and the genetic basis of fitness limits our understanding of adaptive evolution. Among‐year variation in the genetic basis of fitness is rarely quantified, and estimates of selection are typically based on single components of fitness, thus potentially missing conflicting selection acting during other life‐history stages. Here, we examined among‐year variation in selection on a key life‐history trait and the genetic basis of fitness covering the whole life cycle in the annual plant Arabidopsis thaliana . We planted freshly matured seeds of >200 recombinant inbred lines ( RIL s) derived from a cross between two locally adapted populations (Italy and Sweden), and both parental genotypes at the native site of the Swedish population in three consecutive years. We quantified selection against the nonlocal Italian genotype, mapped quantitative trait loci ( QTL ) for fitness and its components, and quantified selection on timing of germination during different life stages. In all 3 years, the local Swedish genotype outperformed the nonlocal Italian genotype. However, both the contribution of early life stages to relative fitness, and the effects of fitness QTL varied among years. Timing of germination was under conflicting selection through seedling establishment vs. adult survival and fecundity, and both the direction and magnitude of net selection varied among years. Our results demonstrate that selection during early life stages and the genetic basis of fitness can vary markedly among years, emphasizing the need for multiyear studies considering the whole life cycle for a full understanding of natural selection and mechanisms maintaining local adaptation.

Biorefinery of the macroalgae Ulva lactuca: extraction of proteins and carbohydrates by mild disintegration - P. R. Postma; O. Cerezo-Chinarro; R. J. Akkerman; G. Olivieri; R. H. Wijffels; W. A. Brandenburg; M. H. M. Eppink (Journal of Applied Phycology, 2018)

Influence of Sewered Versus Septic Systems on Watershed Exports of E. coli - G. Iverson; C. P. Humphrey; M. H. Postma; M. A. O’Driscoll; A. K. Manda; A. Finley (Water, Air, & Soil Pollution, 2017)

Frames of reference and categorical/coordinate spatial relations in a “what was where” task - Francesco Ruotolo; Tina Iachini; Gennaro Ruggiero; Ineke J. M. van der Ham; Albert Postma (Experimental Brain Research, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

First confirmed record of a leucistic Antarctic fur seal pup born outside the Scotia Arc Islands - M. Wege; M. Postma; C. A. Tosh; P. J. N. de Bruyn; M. N. Bester (Polar Biology, 2015)

Maternal environment affects the genetic basis of seed dormancy in A rabidopsis thaliana - Froukje M. Postma; Jon Ågren (Molecular Ecology, 2015)
The genetic basis of seed dormancy, a key life history trait important for adaptive evolution in plant populations, has yet been studied only using seeds produced under controlled conditions in greenhouse environments. However, dormancy is strongly affected by maternal environmental conditions, and interactions between seed genotype and maternal environment have been reported. Consequently, the genetic basis of dormancy of seeds produced under natural field conditions remains unclear. We examined the effect of maternal environment on the genetic architecture of seed dormancy using a recombinant inbred line ( RIL ) population derived from a cross between two locally adapted populations of Arabidopsis thaliana from Italy and Sweden. We mapped quantitative trait loci ( QTL ) for dormancy of seeds produced in the greenhouse and at the native field sites of the parental genotypes. The Italian genotype produced seeds with stronger dormancy at fruit maturation than did the Swedish genotype in all three environments, and the maternal field environments induced higher dormancy levels compared to the greenhouse environment in both genotypes. Across the three maternal environments, a total of nine dormancy QTL were detected, three of which were only detected among seeds matured in the field, and six of which showed significant QTL × maternal environment interactions. One QTL had a large effect on dormancy across all three environments and colocalized with the candidate gene DOG 1 . Our results demonstrate the importance of studying the genetic basis of putatively adaptive traits under relevant conditions.

Objective allergy markers and risk of cancer mortality and hospitalization in a large population-based cohort - Niloofar Taghizadeh; Judith M. Vonk; Jeannette J. Hospers; Dirkje S. Postma; Elisabeth G. E. de Vries; Jan P. Schouten; H. Marike Boezen (Cancer Causes & Control, 2015)

Modelling root–soil interactions using three–dimensional models of root growth, architecture and function - Vanessa M. Dunbabin; Johannes A. Postma; Andrea Schnepf; Loïc Pagès; Mathieu Javaux; Lianhai Wu; Daniel Leitner; Ying L. Chen; Zed Rengel; Art J. Diggle (Plant and Soil, 2013)

Modelling root plasticity and response of narrow-leafed lupin to heterogeneous phosphorus supply - Ying L. Chen; Vanessa M. Dunbabin; Johannes A. Postma; Art J. Diggle; Kadambot H. M. Siddique; Zed Rengel (Plant and Soil, 2013)

Superior spatial touch: improved haptic orientation processing in deaf individuals - Rick van Dijk; Astrid M. L. Kappers; Albert Postma (Experimental Brain Research, 2013)

The role of Streptococcus pneumoniae in community-acquired pneumonia among adults in Europe: a meta-analysis - M. H. Rozenbaum; P. Pechlivanoglou; T. S. Werf; J. R. Lo-Ten-Foe; M. J. Postma; E. Hak (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Genome-wide study identifies two loci associated with lung function decline in mild to moderate COPD - Nadia N. Hansel; Ingo Ruczinski; Nicholas Rafaels; Don D. Sin; Denise Daley; Alla Malinina; Lili Huang; Andrew Sandford; Tanda Murray; Yoonhee Kim; Candelaria Vergara; Susan R. Heckbert; et al. (Human Genetics, 2013)

The Marine Mammal Programme at the Prince Edward Islands: 38 years of research - MN Bester; PJN de Bruyn; WC Oosthuizen; CA Tosh; T McIntyre; RR Reisinger; M Postma; DS van der Merwe; M Wege (African Journal of Marine Science, 2011)

Phenotypic variability and modelling of root structure of wild Lupinus angustifolius genotypes - Ying Long Chen; Vanessa M. Dunbabin; Johannes A. Postma; Art J. Diggle; Jairo A. Palta; Jonathan P. Lynch; Kadambot H. M. Siddique; Zed Rengel (Plant and Soil, 2011)

Frames of reference and categorical and coordinate spatial relations: a hierarchical organisation - Francesco Ruotolo; Tina Iachini; Albert Postma; Ineke J. M. van der Ham (Experimental Brain Research, 2011)

Soil biota community structure and abundance under agricultural intensification and extensification - Maria B. Postma-Blaauw; Ron G. M de Goede; Jaap Bloem; Jack H. Faber; Lijbert Brussaard (Ecology, 2010)
Understanding the impacts of agricultural intensification and extensification on soil biota communities is useful in order to preserve and restore biological diversity in agricultural soils and enhance the role of soil biota in agroecosystem functioning. Over four consecutive years, we investigated the effects of agricultural intensification and extensification (including conversion of grassland to arable land and vice versa, increased and decreased levels of mineral fertilization, and monoculture compared to crop rotation) on major soil biota group abundances and functional diversity. We integrated and compared effects across taxonomic levels to identify sensitive species groups. Conversion of grassland to arable land negatively affected both abundances and functional diversity of soil biota. Further intensification of the cropping system by increased fertilization and reduced crop diversity exerted smaller and differential effects on different soil biota groups. Agricultural intensification affected abundances of taxonomic groups with larger body size (earthworms, enchytraeids, microarthropods, and nematodes) more negatively than smaller‐sized taxonomic groups (protozoans, bacteria, and fungi). Also functional group diversity and composition were more negatively affected in larger‐sized soil biota (earthworms, predatory mites) than in smaller‐sized soil biota (nematodes). Furthermore, larger soil biota appeared to be primarily affected by short‐term consequences of conversion (disturbance, loss of habitat), whereas smaller soil biota were predominantly affected by long‐term consequences (probably loss of organic matter). Reestablishment of grassland resulted in increased abundances of soil biota groups, but since not all groups increased in the same measure, the community structure was not completely restored. We concluded that larger‐sized soil biota are more sensitive to agricultural intensification than smaller‐sized soil biota. Furthermore, since larger‐sized soil biota groups had lower taxonomic richness, we suggest that agricultural intensification exerts strongest effects on species‐poor soil biota groups, thus supporting the hypothesis that biodiversity has an “insurance” function. As soil biota play an important role in agroecosystem functioning, altered soil biota abundances and functional group composition under agricultural intensification are likely to affect the functioning of the agroecosystem.

Prevalence of antibodies against Ascaris suum and its association with allergic manifestations in 4-year-old children in the Netherlands: the PIAMA birth cohort study - E. Pinelli; S. M. Willers; D. Hoek; H. A. Smit; L. M. Kortbeek; M. Hoekstra; J. Jongste; F. Knapen; D. Postma; M. Kerkhof; R. Aalberse; J. W. B. Giessen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Retraction Note to: Inhaled corticosteroids and long-acting beta-agonists in adult asthma: a winning combination in all? - Dirkje S. Postma; Huib A. M. Kerstjens; Nick H. T. ten Hacken (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Differential effects of non-informative vision and visual interference on haptic spatial processing - Robert Volcic; Joram J. van Rheede; Albert Postma; Astrid M. L. Kappers (Experimental Brain Research, 2008)

RETRACTED ARTICLE: Inhaled corticosteroids and long-acting beta-agonists in adult asthma: a winning combination in all? - Dirkje S. Postma; Huib A. M. Kerstjens; Nick H. T. ten Hacken (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

Keep an eye on your hands: on the role of visual mechanisms in processing of haptic space - Albert Postma; Sander Zuidhoek; Matthijs L. Noordzij; Astrid M. L. Kappers (Cognitive Processing, 2008)

Haptic spatial orientation processing and working memory - Albert Postma; Sander Zuidhoek; Astrid M. L. Kappers; Matthijs L. Noordzij (Cognitive Processing, 2006)

The effect of neuronal morphology and membrane-permeant weak acid and base on the dissipation of depolarization-induced pH gradients in snail neurons - A. Pantazis; P. Keegan; M. Postma; C. J. Schwiening (Pflügers Archiv - European Journal of Physiology, 2006)

DISSOLVING STOCK DISCRETENESS WITH SATELLITE TRACKING: BOWHEAD WHALES IN BAFFIN BAY - M. P. Heide‐JØrgensen; K. L. Laidre; M. V. Jensen; L. Dueck; L. D. Postma (Marine Mammal Science, 2006)
Nine bowhead whales ( Balaena mysticetus ) were instrumented with satellite transmitters in West Greenland in May 2002 and 2003. Transmitters were either encased in steel cans or imbedded in floats attached to wires. Transmitters mounted in steel cans had a high initial failure rate, yet those that were successful provided tracking durations up to seven months. Float tags had a low initial failure rate and initially provided large numbers of positions; however, they had deployment durations of only 2–33 d. All tracked whales departed from West Greenland and headed northwest towards Lancaster Sound in the end of May. Three tags with long tracking durations (197–217 d) recorded movements of whales (1 ♂, 2 ♀) into December in 2002 and 2003. All of these individuals remained within the Canadian High Arctic or along the east coast of Baffin Island in summer and early fall. By the end of October, all three whales moved rapidly south along the east coast of Baffin Island and entered Hudson Strait, an apparent wintering ground for the population. One of the whales did not visit Isabella Bay on east Baffin Island, the locality used for abundance estimation from photographic reidentification of individuals. The movements of whales tagged in this study raise critical questions about the assumed stock discreteness of bowhead whales in Foxe Basin, Hudson Strait, and Davis Strait and indicate current estimates of abundance are negatively biased.

Within-trophic group interactions of bacterivorous nematode species and their effects on the bacterial community and nitrogen mineralization - M. B. Postma-Blaauw; F. T. de Vries; R. G. M. de Goede; J. Bloem; J. H. Faber; L. Brussaard (Oecologia, 2005)

Modeling Continental Shelf Formation in the Adriatic Sea and Elsewhere - Lincoln Pratson; John Swenson; Albert Kettner; Juan Fedele; George Postma; Alan Niedoroda; Carl Friedrichs; James Syvitski; Chris Paola; Mike Steckler; Eric Hutton; Christopher Reed; et al. (Oceanography, 2004)

Improved neuromonitoring during spinal surgery using double-train transcranial electrical stimulation - H. L. Journée; H. E. Polak; M. de Kleuver; D. D. Langeloo; A. A. Postma (Medical & Biological Engineering & Computing, 2004)

Delay improves performance on a haptic spatial matching task - Sander Zuidhoek; Astrid M. L. Kappers; Rob H. J. van der Lubbe; Albert Postma (Experimental Brain Research, 2003)

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)

Genomic organisation and chromosomal localisation of two members of the KCND ion channel family, KCND2 and KCND3 - Alex V. Postma; Connie R. Bezzina; Jeltje F. de Vries; Arthur A. M. Wilde; Antoon F. M. Moorman; Marcel M. A. M. Mannens (Human Genetics, 2000)

Frontal-Lobe Involvement in Spatial Memory: Evidence from PET, fMRI, and Lesion Studies - Roy P. C. Kessels; Albert Postma; Elze M. Wijnalda; Edward H. F. de Haan (Neuropsychology Review, 2000)

Genomic organisation and chromosomal localisation of two members of the KCND ion channel family, KCND2 and KCND3 - Alex V. Postma; Connie R. Bezzina; Jeltje F. de Vries; Arthur A. M. Wilde; Antoon F. M. Moorman; Marcel M. A. M. Mannens (Human Genetics, 2000)

Fluctuating Life-History Parameters Indicating Temporal Variability in Metal Adaptation in Riverine Chironomids - D. Groenendijk; B. van Opzeeland; L. M. Dionisio Pires; J. F. Postma (Archives of Environmental Contamination and Toxicology, 1999)

Control and regulation of metabolic fluxes in microbes by substrates and enzymes - K. van Dam; N. Jansen; P. Postma; P. Richard; G. Ruijter; M. Rutgers; H. P. Smits; B. Teusink; J. van der Vlag; M. Walsh; H. V. Westerhoff (Antonie van Leeuwenhoek, 1993)

Quantitative aspects of glucose metabolism by Escherichia coli B/r, grown in the presence of pyrroloquinoline quinone - R. W. J. Hommes; J. A. Simons; J. L. Snoep; P. W. Postma; D. W. Tempest; O. M. Neijssel (Antonie van Leeuwenhoek, 1991)

Physiological significance and bioenergetic aspects of glucose dehydrogenase - Oense M. Neijssel; Ronald W. J. Hommes; Pieter W. Postma; David W. Tempest (Antonie van Leeuwenhoek, 1989)

The influence of the culture pH value on the direct glucose oxidative pathway in Klebsiella pneumoniae NCTC 418 - R. W. J. Hommes; P. W. Postma; D. W. Tempest; O. M. Neijssel (Archives of Microbiology, 1989)

The separate roles of PQQ and apo-enzyme syntheses in the regulation of glucose dehydrogenase activity in Klebsiella pneumoniae NCTC 418 - R. W. J. Hommes; P. T. D. Herman; P. W. Postma; D. W. Tempest; O. M. Neijssel (Archives of Microbiology, 1989)

Energetics of glucose uptake in Salmonella typhimurium - M. Driessen; P. W. Postma; K. van Dam (Archives of Microbiology, 1987)

The functional significance of glucose dehydrogenase in Klebsiella aerogenes - R. W. J. Hommes; B. van Hell; P. W. Postma; O. M. Neijssel; D. W. Tempest (Archives of Microbiology, 1985)

Virulence ofEscherichia coli strains isolated from urine of patients with acute cystitis and from faeces of healthy women - J. F. van den Bosch; P. Postma; D. van Brenk; P. A. M. Guinée; J. de Graaff; D. M. MacLaren (Antonie van Leeuwenhoek, 1981)

Virulence of Escherichia coli in acute pyelonephritis, acute cystitis and asymptomatic bacteriuria - J. F. van den Bosch; P. L. Oe; P. Postma; J. de Graaff; D. M. MacLaren; W. H. Jansen; P. A. M. Guinée (Antonie van Leeuwenhoek, 1980)

Hemolysis and urinary virulence of Escherichia coli. - J. F. Bosch; P. Postma; J. Graaff; D. M. MacLaren (Antonie van Leeuwenhoek, 1980)

Urinary virulence of E. coli in experimental haematogenous pyelonephritis - J. F. van den Bosch; P. Postma; J. de Graaff; D. M. MacLaren (Antonie van Leeuwenhoek, 1979)